1989
DOI: 10.1152/ajpregu.1989.256.6.r1279
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus in Brattleboro rats: cardiovascular, fluid, and electrolyte status

Abstract: Because plasma arginine vasopressin (AVP) levels are raised during streptozotocin (STZ)-induced diabetes mellitus (DM), it is possible that AVP contributes to the pattern of change in fluid and electrolyte handling and cardiovascular status after STZ treatment. Therefore we have made daily measurements of cardiovascular and metabolic variables in normal (Long-Evans) and AVP-deficient (Brattleboro) rats treated with saline or STZ. Twenty-four days after STZ, both strains had similar weight loss and increases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Bradycardia following STZ treatment has been reported by several authors (e.g. Stuesse et al, 1982;Carbonell et al, 1987;Hebden et al, 1987a;Tomlinson et al, 1989;1990). Tomlinson et al (1990) have shown that Brattleboro (i.e.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Bradycardia following STZ treatment has been reported by several authors (e.g. Stuesse et al, 1982;Carbonell et al, 1987;Hebden et al, 1987a;Tomlinson et al, 1989;1990). Tomlinson et al (1990) have shown that Brattleboro (i.e.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have reported on resting arterial blood pressure following STZ treatment; some have shown diabetic rats are hypertensive (Kawashima et al, 1978;Bunag et al, 1982;Funakawa et al, 1983), whereas others have found they are normotensive (Rodgers, 1986;Yamamoto, 1988) or hypotensive (Kohler et al, 1980;Hebden et al, 1987a;Kusaka et al, 1987;Tomlinson et al, 1989;1990). The difference between the results from this present study and our earlier studies, in which we reported hypotension in diabetic rats (Hebden et al, 1987a,b;Tomlinson et al, 1989;1990), is that previously both systolic and diastolic blood pressures were recorded, and it was systolic pressure which was consistently reduced (Hebden et al, 1987a;Tomlinson et al, 1989). In the present work we also observed a reduction in systolic blood pressure following STZ treatment (data not shown), but we measured electronically-derived mean blood pressure (in order to calculate vascular conductances) and this was not reduced because in the bradycardic, STZ-treated rats the pressure wave form is broader than in control animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, focused mainly on cardiovascular function, glycemia in control LE rats was 7.3 mmol͞l. Glycosuria and renal function were not evaluated (32).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a diminished contribution of vasopressin, possibly due to diminished pressor responsiveness, was suspected during blood pressure recovery following experimentally induced acute hypotension in rats [47]. Finally, when DM is induced in Brattleboro rats genetically lacking vasopressin, they exhibit a fall in blood pressure, a feature not observed in control rats in which vasopressin secretion can increase during DM [48]. If the vascular V1a receptors are not desensitized in DM, the permanent rise in the vasopressin level to which they are exposed might participate, through the vasoconstrictive actions of the hormone, in the cardiovascular and renal complications of DM.…”
Section: V1a and V1b Vasopressin Receptors In Diabetes Mellitusmentioning
confidence: 99%